Injectable DaxibotulinumtoxinA in Cervical Dystonia: A Phase 2 Dose‐Escalation Multicenter Study. Issue 3 (26th April 2018) - Jankovic, Joseph; Truong, Daniel; Patel, Atul T.; Brashear, Allison; Evatt, Marian; Rubio, Roman G.; Oh, Chad K.; Snyder, Daniel; Shears, Gill; Comella, Cynthia
Abstract: Background: Injectable daxibotulinumtoxinA (an investigational botulinum toxin, RT002) may offer a more prolonged duration of response—and therefore less frequent dosing—than onabotulinumtoxinA. Objectives: To perform a phase 2, open‐label, dose‐escalation study to assess the efficacy and safety of daxibotulinumtoxinA in cervical dystonia. Methods: Subjects with moderate‐to‐severe isolated cervical dystonia were enrolled in sequential cohorts to receive a single open‐label, intramuscular dose of injectable daxibotulinumtoxinA of up to 200 U ( n = 12), 200–300 U ( n = 12), or 300–450 U ( n = 13;clinicaltrials.gov identifier NCT02706795). Results: Overall, 33/37 enrollees completed the trial. DaxibotulinumtoxinA was associated with mean reductions in Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS)‐Total score of 16.8 (38%) at week 4, 21.3 (50%) at week 6, and 12.8 (30%) at week 24. The proportion of subjects who were responders (achieved ≥ 20% reduction in TWSTRS‐Total score) was 94% at week 6 and 68% at week 24. The median duration of response (time until > 20% of the improvement in TWSTRS‐Total score achieved at week 4 was no longer retained or re‐treatment was needed) was 25.3 weeks (95% CI, 20.14–26.14 weeks). There were no serious adverse events and there was no apparent dose‐related increase in the incidence of adverse events. The most common treatment‐related adverse events were dysphagia (14%) and injection site erythema (8%). Conclusions: Preliminary assessments suggest that injectable daxibotulinumtoxinA at doses up to 450 U is well tolerated and may offer prolonged efficacy in the treatment of cervical dystonia. Further studies involving larger numbers of patients are now warranted.